COSMO Study on the Heptane-Toluene-DMF/DEG-KSCN Liquid- Liquid Equilibrium System - Souza, Beatriz Fernanda Bonfim de; Lenhare, Stephanie; Heck, Stenio Cristaldo; Zuber, Andre; Beneti, Stephani Caroline; Zanette, Andreia Fatima [UNESP]; Cardozo Filho, Lucio (Amer Chemical Soc, 2021)
The class of aromatic hydrocarbons is one of the most important in the petrochemical industry. As they are in a multicomponent mixture with aliphatics, separation represents a huge challenge given the proximity of their boiling points, and liquid-liquid extraction represents a good alternative to conventional separation processes. In this paper, liquid-liquid equilibrium data of a heptane-toluene-dimethylformamide (DMF)-diethylene glycol (DEG) system in the presence and absence of potassium thiocyanate salt were obtained and used to study solvation of ions in the DMF-DEG polar mixture solvent, using COnductor-like Screening MOdel (COSMO) modeling. It was verified that the solvation complexes failed to describe the system equilibrium despite the otherwise expected. COSMO-RS (realistic solvents) calculations of the unsolvated ions presented better approximation with experimental data compared to COSMO-SAC (segment activity coefficient) ones. The best simulation obtained with nonsolvated ions occurred probably due to pi electron interactions with ion charge and hydrogen bond with the solvent.